Early ripening cycle and yield in coffee genotypes derivatives from C1195-5-6-2 - Andreazi, Elder; Carducci, Fernando Cesar; Sera, Tumoru; Pereira, Carlos Theodoro Motta; Mariucci Junior, Valdir; Carvalho, Filipe Gimenez; Shigueoka, Luciana Harumi; Santos, Willian Gabriel dos; Fonseca, Inês Cristina de Batista; Sera, Gustavo Hiroshi (Coffee Science - ISSN 1984-3909, 2017)
The aim in research study was to identify coffee plants with early and very early ripening cycle with high yield in Arabica coffee progenies carriers of C. racemosa genes. The field trial was carried out on IAPAR in September 2007 in Londrina, PR, Brazil. The experimental design was a randomized blocks design with three replicates and five plants per plot in the spacing of 2.5 x 0.5 m. We evaluated 17 F1RC6 progenies derived from backcrosses of different Arabica coffee genotypes with a F2 plant of the genotype C1195-5-6-2. As comparative controls were used cultivars IAPAR 59, IPR 99 and Catuaí Vermelho IAC 81 which have, respectively, semi-early, semi-late and late ripening cycles. The traits evaluated were yield, vegetative vigor and ripening cycle. The ripening cycle and vegetative vigor assessments were performed using scale grades and yield in volume of fruits. The progenies H0509, H0501, H0518, H0513, H0508, H0510, H0505, H0506, H0514 and H0504 were earlier than their parentals. Among them, the progenies H0518, H0507 and H0508 were more productive than the controls and did not differ for vegetative vigor trait. Ten F1RC6 progenies, carriers of C. racemosa genes, with potential to become cultivars with early and very early cycle were identified. The early ripening cycle trait of C. racemosa, present in C1195-5-6-2 remained after the crossing cycles of C. arabica.